Combined surgery and sclerotherapy for 13 years: a case report of a patient with CLOVES - Wang, Shiqi; Yuan, Siming (Frontiers in Pediatrics, 2024)
Congenital lipomatous overgrowth, vascular malformations, epidermal nevi, and skeletal anomalies (CLOVES) constitute a rare overgrowth disorder resulting from a mosaic function-acquiring mutation in the PIK3CA gene. Targeted drugs for the PI3K-AKT signaling pathway remain under clinical trial and surgery is commonly used to meet both aesthetic and functional requirements for CLOVES patients. We report here the course and experience of a male patient treated at our institution for up to 13 years. The course of treatment consisted of nine anhydrous ethanol sclerotherapy procedures and two segmental trunk mass resections. After undergoing sequential treatment, the patient experienced improved thoracic deformity and scoliosis, enabling him to grow and develop normally.